2021
DOI: 10.1371/journal.pone.0252055
|View full text |Cite
|
Sign up to set email alerts
|

Migratory movements of Atlantic puffins Fratercula arctica naumanni from high Arctic Greenland

Abstract: Although the Atlantic puffin Fratercula arctica is well studied throughout its temperate and low Arctic breeding range, few have studied the species in its far northern distribution. This study is the first to present data on the migratory movements of the “large-billed” subspecies, F. a. naumanni, that breeds in the high Arctic and which has significantly larger body size than those farther south. During 2013–2015, migration tracks were collected from nine adult puffins (6 males and 3 females) tagged with geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Geolocator data from 42 complete migration routes revealed that tufted puffins were short-distance migrants, wintering in the deep GOA and Northeast Pacific waters ~615 km south and southeast of the Middleton Island breeding colony. Similar to Atlantic puffins (Burnham et al, 2021) and Cassin's auklets of British Columbia, Canada (Studholme et al, 2019), our study population of tufted puffins shifted southwards throughout the non-breeding season, ranging from ~560 km from the colony in early winter to ~716 km from the colony during late winter. These results are in contrast to previous evidence suggesting tufted puffins winter south of 40°N and in the central North Pacific Ocean (see International North Pacific Fisheries Commission, 1992, noted in Piatt andKitaysky, 2002).…”
Section: Drivers Of Non-breeding Season Spatial Distributionmentioning
confidence: 53%
See 2 more Smart Citations
“…Geolocator data from 42 complete migration routes revealed that tufted puffins were short-distance migrants, wintering in the deep GOA and Northeast Pacific waters ~615 km south and southeast of the Middleton Island breeding colony. Similar to Atlantic puffins (Burnham et al, 2021) and Cassin's auklets of British Columbia, Canada (Studholme et al, 2019), our study population of tufted puffins shifted southwards throughout the non-breeding season, ranging from ~560 km from the colony in early winter to ~716 km from the colony during late winter. These results are in contrast to previous evidence suggesting tufted puffins winter south of 40°N and in the central North Pacific Ocean (see International North Pacific Fisheries Commission, 1992, noted in Piatt andKitaysky, 2002).…”
Section: Drivers Of Non-breeding Season Spatial Distributionmentioning
confidence: 53%
“…The timing of seasons was determined by a change point analysis for each tracked puffin. breeding colony during throughout the winter (Burnham et al, 2021).…”
Section: Drivers Of Non-breeding Season Spatial Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high genetic similarity to these genetic clusters and lack of detectable admixture with the large Thule birds suggests that these are dispersed individuals from southern natal colonies. Their overwintering areas support a southern origin (Burnham et al 2021), corresponding to their respective genetic clusters and not the regions used by the larger Thule individuals (Fayet et al 2017, Burnham et al 2021, Kersten et al 2021. Specifically, the female from the West Atlantic ESU (ID: 8408 in Burnham et al 2021) overwintered in the Labrador Sea and North Atlantic, corresponding with colonies from Canada (Fayet et al 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Though our limited sample size probably impacts differentiation estimate accuracy, Thule and Spitsbergen are c. 5300 km apart (over water) and the observed patterns align with previous findings of isolation by distance within Puffin Evolutionary Significant Units (ESUs; Kersten et al 2021). Moreover, available tracking data indicate no non-breeding season distribution overlap between birds from these High Arctic colonies (Fayet et al 2017, Burnham et al 2021, Kersten et al 2021 genetically most similar to the Spitsbergen F. a. naumanni, but the two populations should be managed separately given the lack of non-breeding distribution overlap and observed genetic differentiation (Moritz 1994).…”
Section: Discussionmentioning
confidence: 99%